2014
DOI: 10.3892/etm.2014.1506
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of serum leptin and a promising novel diagnostic model for sepsis

Abstract: Diagnosis of sepsis in critically ill patients is important to reduce morbidity and mortality. The present study was conducted to determine the role of serum leptin in the early diagnosis of sepsis and to establish a diagnostic model for sepsis. A retrospective study was conducted of 331 patients from an intensive care unit. All patients underwent consistent blood collection at 6:00 a.m. every morning after fasting. Serum leptin concentrations and additional markers of sepsis were compared between the sepsis g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 33 publications
1
18
0
3
Order By: Relevance
“…1,2 With an increasing incidence, severe sepsis and septic shock are major health pathogenesis of severe sepsis and septic shock has been explained by the excessive production of cytokines, endothelial activation and microvascular thrombosis. 3 The host response to infection involves a complex, organized and coherent interaction between immune, autonomic, neuroendocrine and behavioral systems.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 With an increasing incidence, severe sepsis and septic shock are major health pathogenesis of severe sepsis and septic shock has been explained by the excessive production of cytokines, endothelial activation and microvascular thrombosis. 3 The host response to infection involves a complex, organized and coherent interaction between immune, autonomic, neuroendocrine and behavioral systems.…”
Section: Introductionmentioning
confidence: 99%
“…Newer data demonstrated that leptin have almost of the same relevance in numerous physiological processes, such as regulation of both female and male reproduction, hematopoesis and angiogenesis, glucoregulation, wound healing, inflammation and osteogenesis (25). Furthermore, leptin has a major role in chronic inflammatory mechanism characteristic for obesity and atherosclerosis (26), sepsis (27), chronic viral infection (28) and cancer (29). Leptin exert its action by binding specific membrane receptor (Ob-R), expressed on different cell types, including immune cells (30).…”
Section: Discussionmentioning
confidence: 99%
“…Of all the biomarkers evaluated in this study, only leptin was significantly correlated with the APPLE score, although the correlation was modest. Leptin has been used for distinguishing septic human patients from those that are nonseptic but had clinical symptoms indicative of systemic inflammatory response syndrome . The magnitude of leptin concentration is correlated to disease severity and is probably related to its inherent properties of being an inflammatory mediator.…”
Section: Discussionmentioning
confidence: 99%
“…Leptin has been used in a prognostic model in predicting sepsis in people. Leptin concentration positively correlated with body temperature, heart rate, and creatinine, and when combined with body temperature, white cell count, and heart rate, it was found to be a valuable marker for distinguishing patients that were septic from those that were nonseptic but had systemic inflammatory response syndrome . Two studies have rigorously evaluated ELISA kits for analyzing leptin and adiponectin in canine serum, respectively …”
Section: Introductionmentioning
confidence: 99%